How 'some garlic' becomes 'a garlic' or 'some onion': Mass and count processing in aphasia - Fieder, N.; Nickels, L.; Biedermann, Britta-Andrea; Best, W. (Elsevier Ltd, 2015)
This paper informs our understanding of the representation and processing of mass and count nouns through an investigation of the underlying causes of mass/count specific impairments in in two people with aphasia, DEH and GEC. The factors influencing the production of mass and count nouns and noun phrases was comprehensively assessed. The results showed that GEC's impairment affected mass noun naming, resulting in the production of semantic paraphasias and no responses. In contrast, DEH frequently substituted mass determiners with count determiners leading to ungrammatical noun phrases. In comparison to younger control group, a control group of older adults showed similar difficulties to DEH with mass noun phrases, although less severe, indicating effects of cognitive ageing on lexical and semantic processing. DEH and the elderly controls' results replicate and support previous findings regarding the lexical-syntactic representation of mass/count information. GEC's difficulties extend these findings by providing additional evidence for a semantic component in the representation of countability (e.g., a semantic feature/concept COUNTABLE for count nouns, UNCOUNTABLE for mass nouns) which contributes to mass and count noun selection. GEC's mass noun difficulties are suggested to result from weaker connection strength between noun lemmas and mass concepts compared to count concepts as a result of the overall lower frequency distribution of mass nouns.